Conceptual Risk Framework: Integrating Ecological Risk of Introduced Species with Recipient Ecosystems. (13th November 2019) - Probert, Anna F; Ward, Darren F; Beggs, Jacqueline R; Lin, Sheng-Lin; Stanley, Margaret C
Abstract: Global changes are predicted to facilitate the introduction, establishment, and spread of species into new environments leading to potential negative impacts on local biodiversity. Evaluating the risk associated with introduced species with a high likelihood of arrival, or species that have already been introduced, is therefore increasingly important. In the present article, we outline an operational framework to provide a basis for assessing the ecological risk of introduced species in order to facilitate justifiable management decisions. The framework integrates information based on both the species and the (potential) recipient ecosystems, using existing tools to guide pest managers through the stepwise process. This enables the prediction of high-risk species and the identification of those ecosystems most vulnerable to invasion, and facilitates understanding of the potential mechanisms and magnitude of pest impacts. The framework can be applied to different invasion scenarios to evaluate the risks and impacts of species.